Capture and corporate cooptation: the role of the Mexican Foundation for Health in public health policy - Torres, Christian; Calvillo, Alejandro; Zúñiga, Javier (Frontiers in Political Science, 2024)
Introduction Corporate capture responds to efforts to strengthen regulation or prohibition of commercial determinants of health [tobacco, alcohol, sugar-sweetened beverages, ultra-processed products (UPFs), commercial milk formula, and pharmaceuticals], in an attempt to interfere with public health policies that threaten the commercial, economic, and political interests of major industries. This manuscript proposes the characterization of the corporate capture of public health in Mexico, exercised through the Mexican Foundation for Health (FUNSALUD). Methodology An analysis of FUNSALUD and its stakeholders was carried out under the framework of commercial determinants of health, using a qualitative methodology, and executed in five stages: document analysis from 1985 to 2021; identification and characterization of stakeholders; semi-structured interviews; classification of corporate strategies; and relationship mapping. Results Actors in the pharmaceutical, food, tobacco, alcohol, commercial milk formula, and sugar-sweetened beverage industries were identified as corporate members of FUNSALUD. We identify six corporate strategies used to interfere in public health and food policies, highlighting the role of a revolving door bureaucracy in the case of the Ministry of Health. Conclusion The Mexican Foundation for Health has functioned as a front organization created by the private sector to influence public policy decision-making, protect corporate interests, and oppose international recommendations to combat non-communicable diseases.